2015
DOI: 10.1155/2016/3816256
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Bone Marrow Mesenchymal Stem Cells to Cardiomyocyte‐Like Cells Is Regulated by the Combined Low Dose Treatment of Transforming Growth Factor‐β1 and 5‐Azacytidine

Abstract: Bone marrow mesenchymal stem cells (BMMSCs) are used in cardiac tissue engineering for the regeneration of diseased hearts. We examined the differentiation of rat BMMSCs into cardiomyocyte-like cells when induced with a combined low dose treatment of transforming growth factor-β1 (TGF-β1) and 5-azacytidine (5-AZA). Results showed that cell proliferation in the combined low dose treatment group of TGF-β1 and 5-AZA was increased compared with the TGF-β1 group or the 5-AZA group. The cell apoptosis was relieved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…Within this study, we used 5‐Aza for cardiomyogenic gene profile of differentiated AdMSCs into cardiomyocytes. As a result, unlike Shi et al study, our results showed high level of GJA‐1 gene expression which is an important gap junction protein in heart development. Unlike GJA‐1 gene other tested genes did not showed any significant differences between groups .…”
Section: Discussionmentioning
confidence: 99%
“…Within this study, we used 5‐Aza for cardiomyogenic gene profile of differentiated AdMSCs into cardiomyocytes. As a result, unlike Shi et al study, our results showed high level of GJA‐1 gene expression which is an important gap junction protein in heart development. Unlike GJA‐1 gene other tested genes did not showed any significant differences between groups .…”
Section: Discussionmentioning
confidence: 99%
“…We used Transforming growth factor b1 (TGF-b1) plus 5-Aza-2'-deoxycytidine (5-Aza) to induce myogenic differentiation [12]. For myogenic differentiation, 1×10 5 cells were seeded on 6-well plates, and then cells were treated with combination of TGF-b1 (5 ng/mL, #100-21, PeproTech, USA) plus 5-Aza (5 μmol/L, #11390, Sigma-Aldrich, Germany) for 24 h under normoxic condition (21% O 2 ), then medium was changed for DMEM supplemented with 10% FBS (Gibco), TGF-b1 for continuous 14 days.…”
Section: Induced Differentiation Of Bmscsmentioning
confidence: 99%
“…The ideal effect of stem cell transplantation for tissue damage depends on the cell transplantation rate, differentiation, and paracrine protective factors. Epigenetics in mesenchymal stem cell differentiation has attracted considerable attention, and most investigations have been focused on osteogenic, adipogenic and cardiogenic differentiation [10][11][12], highlighting epigenetic modification in stem cell biology and regenerative medicine [13].…”
Section: Introductionmentioning
confidence: 99%
“…Blockade of ERK1/2 with the specific inhibitor U0126 could inhibit 5‐Aza‐induced expression of cardiac‐specific genes and proteins in hucMSCs . A recent study showed that the differentiation of BM‐MSCs to cardiomyocyte‐like cells driven by 5‐Aza alone or the combination of 5‐Aza and TGF‐β1 was also through activation of ERK1/2 signaling . Other studies have also shown that the activation of ERK1/2 contributes to cardiac differentiation of human and mouse embryonic stem cells …”
Section: Introductionmentioning
confidence: 99%
“…7 A recent study showed that the differentiation of BM-MSCs to cardiomyocyte-like cells driven by 5-Aza alone or the combination of 5-Aza and TGF-β1 was also through activation of ERK1/2 signaling. 8 Other studies have also shown that the activation of ERK1/2 contributes to cardiac differentiation of human and mouse embryonic stem cells. [9][10][11] Many different stimuli, including growth factors, cytokines, transforming agents, and oxidative stress can activate ERK signaling.…”
mentioning
confidence: 97%